Fronteira em expansão: população, terra e família na Zona da Mata mineira. 1808-1850 - Romilda Oliveira Alves (2009)
The purpose of this paper is to study the strategies of patrimony formation of families that populated the central area of the Zona da Mata region in Minas Gerais, during the first half of the 19th century. This investigation is based on Post-mortem inventories, nominative lists, matrimonial processes and note books, among other sources. The analysis of these sources allows one to interpret the structure and composition of the domestic units and their relations of production, focusing on the ways of organizing space and exploring the land. As a result, it is possible to affirm that this area functioned as a privileged place for Portuguese investments and population control as well as a place destined to food production for a dynamic internal market. Moreover, it discusses the importance of family relations to survive in this agricultural border, characterized by agrarian conflicts and land market.